Investigation of bipolar plate materials for proton exchange membrane fuel cells - Shimpalee S. (2017)
© 2016 Hydrogen Energy Publications LLC Low-cost parts, materials, and production methods are important for effective establishment of polymer electrolyte membrane fuel cells (PEMFCs) into the commercial marketplace. The bipolar plate is one part that substantially impacts the PEMFC manufacturing cost. Metallic bipolar plates are an attractive alternative to graphite because they provide the necessary electrical and thermal conductivity and they offer good mechanical strength which supports the forces within the stack. Stainless steel, which is reasonably cheap, a good conductor, and corrosion resistant with high strength, has exhibited acceptable performance as a bipolar plate for several thousand hours of experiments. In this work, a through-mask electro-etching process was selected for fabrication of 304L and 430 stainless steel alloy bipolar plates for 25-cm 2 PEMFC and they were compared against the graphite material. The key results revealed that stainless steel bipolar plates give comparable performance to graphite plates especially under well humidified conditions. At drier conditions, the resistance is the largest factor on the overall performance for all bipolar plate materials. Toray paper and Carbel CL GDLs give different performances under various bipolar plate materials and operating conditions. It is also shown that significant differences in channel depth profiles affect the overall performance.